Assessing Spectator Response to Sport Sponsorships at Historically Black Colleges and Universities - Kelly Patricia Elliott; Beth A. Cianfrone; Timothy Kellison (Journal of Applied Sports Management, 2018)
Historically black colleges and universities (HBCUs) have a strong tradition and football following, yet they struggle financially and lack sponsorship revenue. HBCU fans are understudied, and investigating their behavior would help athletic departments. The purpose of this study was to determine HBCU football consumers’ response to sponsorships. Spectators’ team and university identification, awareness, attitude, loyalty, goodwill, gratitude, and trust of sponsors were examined in relation to purchase intentions and positive word of mouth (WOM) of sponsors. Brand loyalty and gratitude led to increased purchase intentions. Brand attitude, brand awareness, brand loyalty, and goodwill led to positive WOM. Subscribe to JASM
Keywords: HBCU; college athletics; sponsorships; word of mouth; purchase intentions